Internet Utilization and Local Government Procurement for MSEs - Vianita Lianasari Dini; Riatu Mariatul Qibthiyyah (Universitas Udayana, 2026)
This study examines the effect of internet utilization on the proportion of local government procurement transactions allocated to Micro and Small Enterprises (MSEs) through E-Katalog. The dataset covers 504 districts in Indonesia over the period 2020–2023 and is estimated using a Two-Way Fixed Effects (TWFE) model. The results indicate that a one-percentage-point increase in internet utilization is associated with a 0.212-percentage-point rise in the share of local government transactions awarded to MSEs (significant at 0.05%). Heterogeneity analysis reveals a significant effect in Eastern Indonesia (β=0.487; p<0.05) but not in Western Indonesia (β=0.057), suggesting stronger impacts in digitally lagging regions. These findings are consistent with Information Economics and Transaction Cost Theory, highlighting the role of digitalization in reducing information asymmetry and transaction barriers. Overall, this study underscores the importance of expanding internet utilization among MSEs and implementing complementary affirmative policies—such as targeted digital access subsidies and strengthened digital procurement literacy—to promote more inclusive and equitable public procurement for MSEs.Penelitian ini mengkaji pengaruh tingkat utilisasi internet terhadap proporsi transaksi pemerintah daerah kepada Usaha Mikro dan Kecil (UMK) melalui E-Katalog menggunakan data panel pada 504 kabupaten/kota di Indonesia tahun 2020–2023, dengan metode Two-Way Fixed Effect (TWFE). Hasil estimasi menunjukkan bahwa peningkatan 1 poin persentase tingkat utilisasi internet berasosiasi dengan kenaikan 0,212 poin persentase proporsi transaksi pemda kepada UMK (signifikansi 0,05%). Analisis heterogenitas menunjukkan pengaruh signifikan di Indonesia Timur (β=0,487; p<0,05), sementara pengaruhnya tidak signifikan di Indonesia Barat (β=0,057) yang mengindikasikan dampak lebih kuat di wilayah dengan kondisi digital tertinggal. Temuan ini sejalan dengan teori ekonomi informasi dan biaya transaksi, yang menekankan peran digitalisasi dalam menurunkan hambatan informasi dan biaya. Penelitian ini menekankan pentingnya peningkatan utilisasi internet untuk mendorong pengadaan secara daring yang lebih inklusif terhadap UMK, serta perlunya kebijakan afirmatif seperti subsidi biaya berlangganan internet bagi UMK untuk memperluas akses digital dan penguatan literasi sistem digital pengadaan publik (E-Katalog) bagi UMK